Finite Math and Applied Calculus (6th Edition)

Published by Brooks Cole
ISBN 10: 1133607705
ISBN 13: 978-1-13360-770-0

Chapter 0 - Section 0.3 - Multiplying and Factoring Algebraic Expressions - Exercises - Page 21: 43


x=$-\frac{3}{4}$ or $x=\frac{2}{3}$

Work Step by Step

$12x^{2}+x-6$ =$12x^{2}+9x-8x-6$ =$23x(4x+3)-2(4x+3)$ $(4x+3)(3x-2)$$=0$ x=$-\frac{3}{4}$ or $x=\frac{2}{3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.